Experimental study on electrostatic migration of different mineral particles composing lunar dust under electron irradiation - Gan, Hong; Wei, Guangfei; Zhang, Xiao; Xia, Guojun; Shi, Jingjing (Frontiers in Astronomy and Space Sciences, 2023)
Dust electrostatic migration is one of the primary causes of dust events on the surface of airless celestial bodies, which can result in multiple dust phenomena, including lunar horizon glow and dust pools, which offer crucial insights into the evolution of the surface materials of airless celestial bodies. To date, the characteristics and laws of dust electrostatic migration are still not well understood. Here, we report the electrostatic migration characteristics of pyroxene, olivine, and ilmenite particles measured by the laser Doppler method and compare them with the findings of anorthite particles in previous experiments in order to recognize the differential migration characteristics of different mineral components in the lunar dust. The results demonstrate that majority of moving pyroxene and olivine particles have particle sizes that are mostly dispersed in the range of 0 to 10 $\rm{μ m}$, and their vertical velocities are typically less than 2 $\rm{m~s^{-1}}$, which are consistent with the previous studies. The cohesive force between the dust particles is probably what causes the difference in the migration rates of various insulating minerals. Note that no moving ilmenite particles were detected probably due to the material's good conductivity. It can be speculated that the concentration of fugitive dust in the lunar mare is affected by the ilmenite content, but further research is needed to determine how low ilmenite content can cause dust migration.